The Role of Magnetic Fields in Regulating Galaxy Cluster Interactions - Goshu, Belay Sitotaw (Budapest International Research in Exact Sciences (BirEx) Journal, 2024)
Witness the universe evolve in real-time through interactions with galaxy clusters, and colossal structures. In this work, we aim to explore the role of energy distribution and density in disturbed galaxy clusters. The study evolution of energy and density in two-dimensional systems using large-scale numerical simulations. The continuity, momentum, and energy equations were solved in a finite difference time domain to employ magnetic and gravitational fields. The results show that the density distribution is highest in the core and peaks at radii external to this, within galaxy clusters. Meanwhile, the energy density is shown to be reduced at the core and maxima radially outwards where it reaches a maximum around the outer limit of densities. This correlation shows how this gradient in the density modifies its energy distribution. These findings are consistent with prior simulation studies and theoretical models. In conclusion, understanding the dynamics and evolution of galaxy clusters requires understanding density patterns and energy distribution.  More intricate simulations involving extra physical processes like dark matter interactions and magnetic fields should be a part of future efforts.